Reinforcing Capital Expenditures And Regional Revenues For Improving Regional Financial Performance In Kampar Regency - Abdi, Syahrial; Akbar, Bahrullah; Maryani, Dedeh; Sinurat, Marja; Anggaredho, Panji Patra (UNIVERSITAS PAKUAN, 2022)
This study aims to find out how reinforcing capital expenditures and regional revenues can improve regional financial performance in Kampar Regency. Sources of data for this study encompass primary data which includes in-depth interviews with informants and secondary data which includes all documentation relevant to this study such as laws and regulations, articles, reports, etc. The observation period in this study was from 2017-2020 which encompasses three main variables. First, the regional financial performance variable, which is including 4 dimensions: (1) the level of regional financial independence, (2) the level of financial dependence, (3) the degree of decentralization, and (4) the effectiveness of Local Own-source Revenue. Second, the capital expenditures variable is including 1-dimension, fixed asset spending. Third, the regional revenues variable is including to 1 dimension, the regional revenues component. The results of this study are that: (1) the regional financial performance variable in Kampar Regency has a very low level of regional independence, a very high financial dependency, a very low degree of decentralization and a high level of Local Own-source Revenue effectiveness. (2) In the capital expenditures variable, the allocation of capital expenditure to the realization of regional expenditure is still not optimal, with the largest allocation of the construction of roads, irrigation, and networks that are useful for stimulating the economy. Meanwhile. in the aspect of maintaining its assets, the costs set aside are inadequate. (3) Then on the regional revenues variable, the average regional revenues component of Kampar Regency contains (a) Local Own source Revenue (11.03%) which is dominated by contributions from local taxes. (b) Transfer revenue (85.37%) which is dominated by contributions from central government transfers – balancing funds. (c) Other revenue (3.61%). For improving regional financial performance, we propose to carry out a reengineering by reinforcing capital expenditures and regional revenues.